Cardiovascular risk factors among ART‐experienced people with HIV in South Africa. Issue 4 (16th April 2019) - Hyle, Emily P; Bekker, Linda‐Gail; Martey, Emily B; Huang, Mingshu; Xu, Ai; Parker, Robert A; Walensky, Rochelle P; Middelkoop, Keren
Abstract: Introduction: People with HIV (PWH) are at increased risk for atherosclerotic cardiovascular disease (CVD). Screening for CVD risk factors is recommended but not routine in South African HIV clinics. We sought to describe the prevalence of CVD risk factors among antiretroviral treatment (ART)‐experienced patients in South Africa. Methods: We performed a prospective, observational cross‐sectional study of PWH (>21 years, excluding pregnant women) on ART in South Africa. We interviewed patients regarding CVD risk factors, and obtained two blood pressure (BP) measurements and random/fasting glucose via a point‐of‐care glucometer. Standardized chart reviews provided individuals' HIV‐specific data. We defined hypertension as: self‐reported use of antihypertensives or mean systolic BP (SBP) ≥140 mmHg or diastolic BP (DBP) ≥90 mmHg (Stage 1) or SBP ≥160 mmHg or DBP ≥100 mmHg (Stage 2). We defined diabetes as self‐reported use of insulin/oral hypoglycaemics or fasting (random) glucose ≥7.0 (≥11.1) mmol. We obtained risk ratios (RR) for hypertension from a multivariable log‐binomial regression model, adjusting for age, sex and diabetes. Results: From March 2015 to February 2016, 458 participants enrolled with median age 38 years (interquartile range (IQR) 33 to 44 years) and median CD4 466/μL (IQR 317 to 638/μL); 78% were women. Participants were on ART for a median of four years, with 33% on ART ≥6 years. Almost a quarter (106/458) met the study definition for hypertension, of whom 45/106 (42%) were previously diagnosed, 23/45 (51%) were on medication and 4/23 (17%) were controlled. Eight participants had asymptomatic hypertensive urgency (BP≥180/110 mmHg). Of the 458 participants, 26 (6%) met the study definition for diabetes, half of whom (13/26) were already diagnosed; 11/13 (85%) were on treatment, of whom 4/11 (36%) had normal glucose. Age was the only significant predictor of hypertension (RR, 1.04; 95% CI, 1.03 to 1.06, p  < 0.0001) in the multivariable model. Conclusions: Hypertension and diabetes were prevalent among PWH prescribed ART in South Africa with less than half diagnosed, and still fewer treated and controlled. Hypertension was independently associated with age but not with HIV‐specific factors. Screening for and treatment of CVD risk factors could decrease future morbidity and mortality, especially as this population ages.